KETERKAITAN ANATARA STRATEGI MANAJEMEN KONFLIK OLEH KEPALA SEKOLAH DENGAN KINERJA GURU PADA SMA NEGERI 1 LAPPARIAJA KAB. BONE - ARISAL ARISAL (Adaara: Jurnal Manajemen Pendidikan Islam, 2017)
Lingkange strategy organizational conflict management by principals with the performance of teachers at SMAN 1 Lappariaja Kab. Bone.The study aims at examining (1) strategy organizational conflict management by principals and teacher performance, (2) the significant influence of leadership behavior toward lectures performance. This study is a survey research with quantitatif approach. The population is the entire teacher 35 people of SMAN 1 Lappariaja.The sample is selected by simple random sampling by those of the populations, which is 32 people. The variables are devendent variabel is teacher performance and the independent variable is strategy organizational conflict management by principals all are collected by using questionnaire. The data is analyzed by employing descriptive statistic and regression analyses. The results that the strategy organizational conflict management by principals is very good category, and teacher performance is in very good category. The strategy organizational conflict management by principal gives positive influence and significant toward teacher performance.Keywordsi: Strategi managemen konflik, kepala sekolah, kinerja guru.